Cohesiveness is not an adequate theory of general individuation and it does not account for living individuals. (February 2020) - Ayala, David C
Villalobos and Razeto-Barry propose a theory of living individuals that includes both considerations about autopoietic systems and about material individuals. However, I think that their characterisation of individuality is problematic and would not be useful to account for living individuals.